2006
DOI: 10.1002/adfm.200600673
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Weight on the Structure and Morphology of Oriented Thin Films of Regioregular Poly(3‐hexylthiophene) Grown by Directional Epitaxial Solidification

Abstract: Regioregular head‐to‐tail (HT)‐coupled poly(3‐hexylthiophene‐2,5‐diyl) (P3HT) with a weight‐average molecular weight (Mw) in the 7.3–69.6 kDa range is crystallized by directional epitaxial solidification in 1,3,5‐trichlorobenzene (TCB) to yield highly oriented thin films. An oriented and periodic lamellar structure consisting of crystalline lamellae separated by amorphous interlamellar zones is evidenced by atomic force microscopy (AFM) and transmission electron microscopy (TEM). Both the overall crystallinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

42
352
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(396 citation statements)
references
References 34 publications
42
352
2
Order By: Relevance
“…As pointed out in various studies, the width of nanofibrils as well as the lamellar period in epitaxied layers tends first to increase with M n and reach a plateau when M n > 10 kDa. 37,38 This is a typical fingerprint of the onset of chain folding as observed for instance in the case of oligo(urethane)s or polyethylene/ parafins. 39 A second hint for the possibility of P3AT chains to fold lies in the variation of the a-axis parameter (layer period) with increasing M n [see Fig.…”
Section: Chain Foldingmentioning
confidence: 99%
“…As pointed out in various studies, the width of nanofibrils as well as the lamellar period in epitaxied layers tends first to increase with M n and reach a plateau when M n > 10 kDa. 37,38 This is a typical fingerprint of the onset of chain folding as observed for instance in the case of oligo(urethane)s or polyethylene/ parafins. 39 A second hint for the possibility of P3AT chains to fold lies in the variation of the a-axis parameter (layer period) with increasing M n [see Fig.…”
Section: Chain Foldingmentioning
confidence: 99%
“…20 As yet, various studies have clearly demonstrated that P3AT chains tend to fold above a certain M w of 10 kDa. 28,29 Chain folds in P3AT are modeled by a sequence of 7−8 monomer units in cis conformation leading to a 2.0 nm wide fold. Whereas in a crystal structure like PE the interchain interactions with the next-neighbor chains are uniform in the plane perpendicular to the chain, the situation is quite different for P3ATs.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between polymer M W and PCE has been exhaustively studied in 301 P3HT and mixtures with PCBM [49][50][51][52][53][54][55][56][57][58][59][60][61]. We will attempt to briefly summarize the 302 lessons here.…”
mentioning
confidence: 99%